2013
DOI: 10.4103/2230-8210.117223
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-induced parathyroid dysfunction: A new case

Abstract: Lithium salts are widely used in psychiatric practice and are known to induce thyroid dysfunction. Lithium-induced parathyroid dysfunction is rare. We are reporting a case of hyperparathyroidism in a 28-year-old female patient who was on lithium carbonate for 2 years, when she developed osteopenia and girdle girdle-type muscle weakness. Biochemical parameters showed hyperparathyroidism with shift of calcium creatinine clearance ratio to 0.013, indicating an error in threshold of calcium sensing receptor. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A mitotic activity in excess of 5 mitoses per 50 high power microscopic fields, in combination with the presence of foci of coagulative necrosis and macronucleoli, has been proposed as a triad to label parathyroid lesions with a high risk of malignant behavior, in terms of disease recurrence (Bondenson et al 1993). The presence of atypical mitosis and focal areas of necrosis, though considered as criteria of malignancy, has also been described in a minority of atypical parathyroid adenomas (Katz et al 2012, Ricci et al 2012, Nair et al 2013, Ramaswamy et al 2017, Ryhänen et al 2017, Pal et al 2018, Silva-Figueroa et al 2018.…”
Section: :7mentioning
confidence: 99%
“…A mitotic activity in excess of 5 mitoses per 50 high power microscopic fields, in combination with the presence of foci of coagulative necrosis and macronucleoli, has been proposed as a triad to label parathyroid lesions with a high risk of malignant behavior, in terms of disease recurrence (Bondenson et al 1993). The presence of atypical mitosis and focal areas of necrosis, though considered as criteria of malignancy, has also been described in a minority of atypical parathyroid adenomas (Katz et al 2012, Ricci et al 2012, Nair et al 2013, Ramaswamy et al 2017, Ryhänen et al 2017, Pal et al 2018, Silva-Figueroa et al 2018.…”
Section: :7mentioning
confidence: 99%
“…Lithium treatment was also closely associated with hyperparathyroidism and hypercalcaemia. A case report revealed that a 28-year-old female patient who receiving Li 2 CO 3 for bipolar mood disorder for at least 2 years developed hyperparathyroidism (Nair et al, 2013). In a cohort study, it was found that bipolar patients with lithium treatment had higher odds of hypercalcaemia as compared to those not receiving lithium treatment (Meehan et al, 2018).…”
Section: Challenge For the Use Of Lithiummentioning
confidence: 99%
“…Lithium, which has been in clinical use since 1950 [1-2], is one of the cornerstone treatments for bipolar disorder. Although lithium salts are known to disrupt thyroid function [3], lithium-induced parathyroid dysfunction is rare.…”
Section: Discussionmentioning
confidence: 99%